1997
DOI: 10.1007/bf01261959
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation and climatic history of southwest Africa: A marine palynological record of the last 300,000 years

Abstract: Abstract.A continuous palynological record from the marine core GeoB1016-3 from the Angola Basin reveals the regional vegetation and climate history of the last 300 ka. Pollen and spores found at the studied site have their source areas in the different vegetation zones of the adjacent part of the West African continent. Those vegetation zones comprise tropical rain forest, coastal mangrove swamp, Miombo woodland, dry forest, Afromontane forest, desert and semi-desert. The main pollen transport agent is the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Furthermore, this is not a unique feature to the Malawi watershed. Comparison of the Lake Malawi pollen record with those from marine core records covering the last~300 ka off of West and East Africa, we observe that the expansion of afromontane taxa, such as Podocarpus, occurred at the sub-continental scale ( Figure 5; Dupont et al, 2011;Ning & Dupont, 1997). In fact, the timing of the most recent large-scale increase in Podocarpus in all three records is coeval, lasting from about 115 to 90 ka, the beginning of the last glacial period.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Furthermore, this is not a unique feature to the Malawi watershed. Comparison of the Lake Malawi pollen record with those from marine core records covering the last~300 ka off of West and East Africa, we observe that the expansion of afromontane taxa, such as Podocarpus, occurred at the sub-continental scale ( Figure 5; Dupont et al, 2011;Ning & Dupont, 1997). In fact, the timing of the most recent large-scale increase in Podocarpus in all three records is coeval, lasting from about 115 to 90 ka, the beginning of the last glacial period.…”
Section: Resultsmentioning
confidence: 81%
“…White (1983) Podocarpus % 0 20 40 60 80 F I G U R E 5 Percentages of Podocarpus, a dominant afromontane tree, at three sites that straddle southern Africa. Records from the Atlantic Ocean (11°46 0 S, 11°41 0 E) and Indian Ocean (26°10 0 S, 34°01 0 E) are based on marine cores from Ning and Dupont (1997;GeoB-1016) and Dupont et al (2011;Limpopo River Delta) [Colour figure can be viewed at wileyonlinelibrary.com] although barriers to dispersal exist today that isolate a single mountaintop, it is plausible that in the past, certain taxa may have occupied continuous lowland corridors, allowing for greater dispersal. It has been suggested that this might have occurred during recent glacial periods, when cooler temperatures allowed cold-adapted montane species to thrive in the lowlands (Hamilton, 1981;White, 1981).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous high‐resolution geochemical studies at site GeoB 1008 on the southern Congo deep‐sea fan [ Schneider et al , 1994, 1997b] suggest that organic sedimentation over the last 200 kyrs was governed by orbital‐forced fluctuations in atmospheric circulation that triggered upwelling and marine productivity along the western equatorial African continental margin as well as continental aridity‐humidity cycles [ Pokras and Mix , 1985; deMenocal , 1995]. The dominance of precessional‐forced insolation changes on African climate and thus on the distribution of vegetation zones has been confirmed by numerous marine pollen records from the eastern equatorial Atlantic [e.g., Frédoux , 1994; Ning and Dupont , 1997; Jahns et al , 1998; Dupont , 1999; Dupont et al , 2000]. The general link between organic sedimentation and orbital forcing persisted over the past 1.2 Myrs on the Congo deep‐sea fan [ Holtvoeth et al , 2001].…”
Section: Introductionmentioning
confidence: 99%